The Italian parliamentary debate on the riproductive techniques. - Di Pietro, Maria Luisa; Casini, Marina (Medicina e Morale, 2002)
The Italian Chamber of deputies approved in June 2002 a bill now to be submitted to the scrutiny of the Senate. The present paper examines first the history of the bill from the IXth legislature, recording not only the parliamentary passages but also the contributions of the jurisprudence, of the Govern, of several Committees and social movements. The bill is then examined in its most important features. The principle of the priority of the interest/right of the unborn child is consistently applied: in the protection of the new human being from the fertilisation to the birth (right to life), during which period every manipulation of its genetic characteristics is forbidden (right to genetic identity); then in the protection of its right to a family, according to which biological, affective and legal parenthood must coincide (right to psychological and existential identity). Some ethical reservations however remain with regard to the dignity of the procreating act and to the inadequate protection of the unborn's right to a family founded on marriage, whose respect would have given a better guarantee of the stability of parental affection (the bill, on the contrary, gives access to cohabiting couples). Some reservations remain also with regard to the loss of embryos due to the low percentage of success of riproductive techniques. Still, in its main features, the bill deserves appreciation. One must also remember the possibility of conscientious objection, which the bill foresees and which gets all its importance with regard to the significance of giving and been given birth.